Distinct Functions of Bombyx mori Peptidoglycan Recognition Protein 2 in Immune Responses to Bacteria and Viruses - Jiang, Liang; Liu, Weiqiang; Guo, Huizhen; Dang, Yinghui; Cheng, Tingcai; Yang, Wanying; Sun, Qiang; Wang, Bingbing; Wang, Yumei; Xie, Enyu; Xia, Qingyou (Frontiers in Immunology, 2019)
Peptidoglycan recognition protein (PGRP) is an important pattern recognition receptor in innate immunity that is vital for bacterial recognition and defense in insects. Few studies report the role of PGRP in viral infection. Here we cloned two forms of PGRP from the model lepidopteran Bombyx mori: BmPGRP2-1 is a transmembrane protein, whereas BmPGRP2-2 is an intracellular protein. BmPGRP2-1 bound to diaminopimelic acid (DAP)-type peptidoglycan (PGN) to activate the canonical immune deficiency (Imd) pathway. BmPGRP2-2 knockdown reduced B. mori nucleopolyhedrovirus (BmNPV) multiplication and mortality in cell lines and in silkworm larvae, while its overexpression increased viral replication. Transcriptome and quantitative PCR (qPCR) results confirmed that BmPGRP2 negatively regulated phosphatase and tensin homolog (PTEN). BmPGRP2-2 expression was induced by BmNPV, and the protein suppressed PTEN-phosphoinositide 3-kinase (PI3K)/Akt signaling to inhibit cell apoptosis, suggesting that BmNPV modulates BmPGRP2-2-PTEN-PI3K/Akt signaling to evade host antiviral defense. These results demonstrate that the two forms of BmPGRP2 have different functions in host responses to bacteria and viruses.